CSR BENCHMARKING IN THE ROMANIAN BUSINESS AND ACADEMIC SECTOR OF CLUJ-NAPOCA REGION - Alexandra GOGOZAN; Marinela GHEREŞ (Management & Marketing)
The challenge of the present article was to create an index or otherwise a database of CSR contributions that can be quantified and which should clarify the position of a company on the ladder of CSR, and also would enhance the comparability of efforts undertaken by socially responsible companies an institutions. 22 CSR aspects were taken into consideration concerning the interests of the banking sector, the commercial and academic sector, from Cluj-Napoca region, Romania. The benchmarking analysis took into consideration CSR aspects such as economical, environmental and social sustainability, the three pillars of sustainable development. The CSR aspects referred to all the stakeholders involved in those three sectors: employees, suppliers, costumers, community, shareholders and competitors.